Analisis Kesulitan Penyelesaian Soal-Soal Materi Kalor Dengan Teori Polya - I Wayan Sukarjita; Jannes Bastian Selly; Amiruddin Supu; Herni Maya Asbanu (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
This study aims to determine the difficulties experienced by students in solving questions on heat material with Polya’s theory. The method used in this research is descriptive qualitative. The subjects in this study were 28 students of class XI IPA4 SMA Negeri 4 Kota Kupang. The reseach instrument used were test questions and questionnaires. The results shown in this study, namely the difficuly of solving problems with polya’s theory, show that there are 67% of students having difficultyin in understanding the ploblems, 43% of students having difficulties in making plans, 67% of students experiencing problems in carrying out planning solutions to problems that have been solved. Made and 87% of students experienced problems in the re-checking stage.